Hubungan antara Kualitas dan Kepuasan Pelanggan dalam Pembentukan Intensi Pembelian Konsumen : Studi pada Empat Industri Jasa di Semarang - Sulistyo, Heru (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1999)
This research discussed relationship between service quality and consumers satisfaction in term of consumers purchase intention at four service industries in Semarang. The appearance of conflicts among researchers concerning to the relationships between the service quality, consumers satisfaction in the one side and the purchase intentions in the other side previously, brought about the interest to find out the relationship among the three variables concerned, by giving alternatives toward consumers satisfaction as the moderator variable. The objective of the research is to examine the nature of the relationship between service quality and consumers satisfaction in term of the purchase intentions. Based on the model proposed by Taylor and Baker ( I 994), the relations.hip between service quality and purchase intentions was moderated by the consumers satisfaction giving more explanation on the purchase intentions variance better than each variable.The method of data collecting was done through questionares, which consist of 320 respondents at four service industries and using convenience sampling. Those four service industries were familiar for service user. The result of the research showed that coefficient regression of the interaction for the two service industries was positif and signifficant (p £ O. 05), whereas for the the other two was not signifficant. The value of R2 for two service industries was increasing after the interaction of service quality and consumers satisfaction being participated in the model of moderator regression equality and the result supported the research hypotesis. The research also showed that consumers satisfaction (moderator vari able) was able to moderate the relationship between service quality and consumers purchase intention.